Identification of Plasmonic Absorption Profile in Surface Plasmon Microscopy Using Morphology - Bei Zhang; Chengqian Zhang; Qiusheng Wang; Peng Yan; Jing Wang (IEEE Photonics Journal, 2018)
Surface plasmon microscopy (SPM) provides the capability of measuring surface properties of subnanometer layers within the diffraction limited order. In a typical SPM, small changes correspond to surface plasmons (SPs) absorption profile variations on a reflecting back focal plane (BFP), which can be monitored in real-time. However, the lack of fast and high-accurate identification method on SPs profiles has posed significant challenges on objective-coupled SPM instruments, and also limited their practical applications in fast phenomenon sensing and image batch processing. Here we propose a morphological method to identify the SPs absorption profiles. It can extract the SPs profile information from experimentally recorded BFP images with low quality properly and automatically. Experimental verification and further discussions are included.